Implementasi Literasi Digital dalam Mata Kuliah Bahasa Indonesia Berbasis Kearifan Lokal - Suprihatma Suprihatma (Journal on Education, 2023)
Digital literacy is the knowledge and skills to perceive and understand information through digital media. The information received can be used and utilized in an intelligent, careful, healthy, wise and law-abiding manner. Students need these digital literacy skills to master various subjects, especially Indonesian language courses such as listening, speaking, reading and writing. Local wisdom-based digital literacy is an interesting innovation in raising today's millennial generation students. Utilization of aspects of local wisdom will create a positive impression because it can be aligned with digital literacy using technology. It also aims to increase the local value of an area in understanding literacy. Therefore, this study aims to utilize digital literacy in learning Indonesian based on local wisdom. This is useful for maintaining and preserving culture and helping students face increasing challenges. The method used in this research is classroom action research. Classroom Action Research as an improvement activity ranging from problems that arise in learning situations to learning practices of learning activities. In this study, the authors used a research model that refers to the research implementation process proposed by Hobbs which includes accessing, analyzing and evaluating, creating, reflecting and acting. The results of the study show that in the end students realize that the laptops and gadgets they use actually offer many benefits and certainly support the learning process, especially Indonesian.